2019
DOI: 10.1002/polb.24824
|View full text |Cite
|
Sign up to set email alerts
|

Effect of side chain and backbone length on lamellar spacing in polystyrene‐block‐poly(dimethyl siloxane) brush block copolymers

Abstract: We report the synthesis of polystyrene‐block‐poly(dimethyl siloxane) (PS‐b‐PDMS) brush block copolymers (BBCPs) through sequential ROMP of norbornene‐modified macromonomers (‐NB) and explore the effect of side chain length (Nsc) and total backbone degree of polymerization (Nbb) on the self‐assembly of lamellar morphologies. Group I (PS‐NB Mn = 2.9 kg/mol, PDMS‐NB Mn = 4.8 kg/mol) exhibits asymmetric side chains, while Group II (PS‐NB Mn = 4.7 kg/mol, PDMS‐NB Mn = 4.8 kg/mol) possess a more symmetric arrangemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Investigations into bulk materials shown that symmetry between the side chain lengths stabilizes the lamellar phase. 41 PGMEA is a nearly equally good solvent for both blocks resulting in equivalent degree of stretching for both side chains relative to the melt. This will increase the native asymmetry between the two phases.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Investigations into bulk materials shown that symmetry between the side chain lengths stabilizes the lamellar phase. 41 PGMEA is a nearly equally good solvent for both blocks resulting in equivalent degree of stretching for both side chains relative to the melt. This will increase the native asymmetry between the two phases.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the difference in chain length between the PLA and PS side chains, this results in nearly equivalent radii for both portions of the chain. Investigations into bulk materials have shown that symmetry between the side chain lengths stabilizes the lamellar phase . PGMEA is a nearly equally good solvent for both blocks resulting in equivalent degree of stretching for both side chains relative to the melt.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, there has been no previous report in the refereed literature on the T g ‐confinement behavior of bottlebrush polymer in nanoscale thick films. With advancements in synthetic techniques over the past two decades, a wide range of bottlebrush polymers have been synthesized [ 53–87 ] and various potential applications have been advanced based on bottlebrush structures and properties, [ 82–88 ] for example, polymer photonics, [ 82 ] supersoft/superelastic materials, [ 83–85 ] self‐assembly for nanopatterning, [ 86 ] and artificial tissues that are both firm and soft. [ 87 ] Thus, investigating bottlebrush behavior under conditions of nanoscale confinement may be important not only for advancing the scientific understanding of polymer topology‐property effects, including confinement effects, but also for advancing the applications of bottlebrushes.…”
Section: Introductionmentioning
confidence: 99%
“…Bottlebrush polymers are an exceptionally versatile polymer architecture for self-assembly and possess an expansive set of molecular parameters that can be tuned. In addition to molecular parameters present in linear architectures like block fractions and Flory–Huggins χ parameters, bottlebrush polymers can be designed with different grafting densities, side-chain lengths, shapes, and composition gradients. , Multiblock architectures, such as ABC triblock bottlebrushes, have also begun to be explored. ,, This vast range of parameters permits nearly endless variation in the design of bottlebrush polymers and should permit the self-assembly of a wide range of different phases. Though the phase behavior of bottlebrush polymers across this vast parameter space is still being explored, all classical phases, including lamellar, ,,, cylindrical, ,,,, spherical, , and gyroid morphologies have been observed in bottlebrush block polymers, albeit with varying degrees of order.…”
mentioning
confidence: 99%